METODE PEMBELAJARAN UNTUK MENINGKATKAN DAYA SERAP MAHASISWA - Nurmavita Putri Lianingsih; Enung Hasanah (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
Abstract: The Covid-19 pandemic requires the learning process to be carried out online. Online learning is a new thing for students in Indonesia. This study aims to explore learning methods that can increase student absorption. The research method uses qualitative methods. Several methods at Ahmad Dahlan University are one way to increase student absorption; in addition to the blended learning method in several study programs at the university, group activities will make students more active in the assigned tasks. Intense communication between lecturers and students can effectively improve students' absorption ability. Student activity and student participation are essential in the learning process in the classroom, significantly increasing absorption more optimally.Â Abstrak: Pandemi Covid-19 mengharuskan proses pembelajaran dilakukan secara daring. Hal ini termasuk hal baru bagi mahasiswa di Indonesia. Penelitian ini bertujuan untuk mengeksplorasi metode pembelajaran yang dapat meningkatkan daya serap mahasiswa. Metode penelitian menggunakan metode kualitatif. Beberapa metode di Universitas Ahmad Dahlan menjadi salah satu cara untuk meningkatkan daya serap mahasiswa, selain itu metode blended learning pada beberapa program studi di universitas, aktivitas kelompok akan membuat mahasiswa semakin aktif dalamÂ  tugas yang diberikan. Komunikasi Dosen dan Mahasiswa yang intens dapat meningkatkan kemampuan daya serap mahasiswa lebih efektif. Keaktifan Mahasiswa dan keikutsertaan Mahasiswa sangat penting dalam proses pembelajaran di kelas terutama untuk peningkatan daya serap lebih optimal.